2022
DOI: 10.3390/foods11030484
|View full text |Cite
|
Sign up to set email alerts
|

Mineral Composition and Bioaccessibility in Rocket and Purslane after Zn Biofortification Process

Abstract: Zinc (Zn) is an essential key nutrient in different biochemical and physiological processes. The nutritional deficit of this mineral element is estimated to affect the health of over 3 billion people worldwide. Several strategies are available to reduce the negative impact of mineral malnutrition; among them, biofortification is the practice of deliberately increasing the nutrients and healthy compounds in the edible parts of vegetables. This study aims to evaluate Zn bioaccessibility in biofortified and non-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 46 publications
0
17
0
Order By: Relevance
“…The release of nutrients (the bioaccessible fraction) in the intestinal tract during the digestive process of plant materials depends on a variety of factors, such as the species and the type of plant materials, the localization of the nutrient, and it is affected by a host of variables such as the concentrations of other nutrients and/or anti-nutritional compounds, the cooking method used, if and how the food has been processed, and the interaction of other nutrients. The concentration of the nutrient in the edible parts is important, but even the biofortification process can modify the release of nutrients, as has been reported by a number of studies regarding different mineral elements ( 12 , 21 , 47 , 51 , 52 , 76 ).…”
Section: Bioavailability and Bioaccessibility: A Useful Support Tool ...mentioning
confidence: 98%
See 2 more Smart Citations
“…The release of nutrients (the bioaccessible fraction) in the intestinal tract during the digestive process of plant materials depends on a variety of factors, such as the species and the type of plant materials, the localization of the nutrient, and it is affected by a host of variables such as the concentrations of other nutrients and/or anti-nutritional compounds, the cooking method used, if and how the food has been processed, and the interaction of other nutrients. The concentration of the nutrient in the edible parts is important, but even the biofortification process can modify the release of nutrients, as has been reported by a number of studies regarding different mineral elements ( 12 , 21 , 47 , 51 , 52 , 76 ).…”
Section: Bioavailability and Bioaccessibility: A Useful Support Tool ...mentioning
confidence: 98%
“…The gastrointestinal digestion model has been used to identify the biofortified species or treatments (agronomic and/or food processing) that are able to release high quantities of silicon ( 12 ), Ca ( 52 ), zinc ( 76 , 77 ), selenium ( 78 ), iodine ( 79 ), iron ( 80 ) in the intestinal tract. Thus, bioaccessibility assessment methodologies can be used to select the species, cultivars and/or genotypes that are able to release high quantities of nutrients during the digestion process in order to maximize the health effects of the biofortification process.…”
Section: Bioavailability and Bioaccessibility: A Useful Support Tool ...mentioning
confidence: 99%
See 1 more Smart Citation
“…71 Zinc is critical in the maintenance of human health, participating in the synthesis and transmission of neurotransmitters and regulating the immune system activity. 72,73 The intake of zinc may have a negative correlation with depression. 74 Zinc alleviated the depression-like behavior of rats induced by lipo-…”
Section: Food and Function Reviewmentioning
confidence: 99%
“…This fruit is interesting, since it has also antimicrobial activity, as confirmed in the reported study against multidrug-resistant microorganisms, Escherichia coli and Klebsiella pneumoniae strains, isolated from poultry. D’Imperio et al [ 5 ] studied the biofortification process of rocket and purslane with Zn. A bioaccessibility study of this nutrient using an in vitro gastrointestinal digestion process confirmed that it is possible to obtain a high content of Zn biofortified rocket and purslane by adopting an appropriate mineral plant nutrition solution enriched with this nutrient.…”
mentioning
confidence: 99%